EFEKTIVITAS PEMBELAJARAN PAI DALAM MENINGKATKAN EMOTIONAL INTELLIGENCE SISWA DI SMK NEGERI 1 CIKARANG BARAT - Nur Afifah, Siti; Ghofur, Abdul (Turats, 2023)
The purpose of this research is to evaluate the effectiveness of Islamic Education learning in enhancing the emotional intelligence of students at SMK Negeri 1 Cikarang Barat. This research is motivated by the fact that in everyday life, not all problems can be solved solely with intellectual abilities. There is a tendency that the higher someone's level of intellectual intelligence, without being accompanied by emotional awareness, the greater the risk of experiencing emptiness or a spiritual drought in that individual. The type of research used is qualitative research. The research results can be summarized as follows: 1) The emotional intelligence of students at SMK Negeri 1 Cikarang Barat varies, with some students having low emotional intelligence and others having high emotional intelligence. 2) The effectiveness of Islamic Education learning in enhancing students' emotional intelligence at SMK Negeri 1 Cikarang Barat can be observed through the activities implemented in Islamic Education, such as counseling, teaching religious values, and religious practices. This indicates that Islamic religious education at SMK Negeri 1 Cikarang Barat is effective in developing an understanding of religion and motivating students to apply religious values in their daily lives, not just focusing on theoretical knowledge but also on the experiential and practical aspects of Islamic religion in students' lives.